A Comparative Study of Terrestrial Laser Scanning and Photogrammetry: Accuracy and Applications - Zakaria, Mohamed H.; Fawzy, Hossam; El-Beshbeshy, Mohammed; Farhan, Magda (Salehan Institute of Higher Education, 2025)
This study presents a comprehensive comparative analysis of Terrestrial Laser Scanning (TLS) and Digital Close-Range Photogrammetry (DCRP) against traditional Total Station (TS) methods for 3D spatial documentation across a range from 8.00 meters to 2.00 mm. The analysis was conducted through three scenarios: Ground Control Points (GCPs), the Kafrelsheikh University Mosque, and Kafr El Sheikh Tanta Road. Paired t-tests and ANOVA revealed statistically significant differences (p < 0.05) across all variables, with TLS demonstrating superior precision. TLS deviations in linear distance measurements were as low as 2 mm compared to TS, while DCRP exhibited variations ranging from 0.02 m to 0.30 m depending on surface reflectivity and distance. Pearson correlation coefficients exceeded 0.95 for TLS across all axes (X, Y, Z), highlighting its reliability. DCRP, while slightly less consistent, showed minor variability, particularly in the Z-axis. For road crack measurements, TLS captured lengths ranging from 180 mm to 750 mm (mean = 501.417 mm, SD = 207.341 mm), which aligned closely with DCRP results (mean = 504.867 mm, SD = 204.455 mm). The mosque’s complex geometry showcased TLS's higher precision (ANOVA F = 15.78, p = 0.0001 for the Y-axis), while DCRP provided faster data acquisition and reduced costs. Both methods demonstrated significant statistical alignment, though TLS consistently outperformed DCRP in accuracy, especially for intricate structures requiring high precision. The findings emphasize the complementary strengths of TLS and DCRP, recommending their integration to achieve an optimal balance of accuracy, efficiency, and cost-effectiveness. Future research should focus on improving the precision of DCRP for detailed architectural and structural documentation while exploring hybrid techniques to enhance the reliability and scalability of 3D surveying methods. Doi: 10.28991/CEJ-2025-011-03-021 Full Text: PDF